2017
DOI: 10.1556/2006.6.2017.058
|View full text |Cite
|
Sign up to set email alerts
|

Social media addiction: What is the role of content in YouTube?

Abstract: BackgroundYouTube, the online video creation and sharing site, supports both video content viewing and content creation activities. For a minority of people, the time spent engaging with YouTube can be excessive and potentially problematic.MethodThis study analyzed the relationship between content viewing, content creation, and YouTube addiction in a survey of 410 Indian-student YouTube users. It also examined the influence of content, social, technology, and process gratifications on user inclination toward Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
147
0
13

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 195 publications
(164 citation statements)
references
References 84 publications
4
147
0
13
Order By: Relevance
“…In the literature, PSMU has been investigated in relation to specific SMSs such as Facebook (Andreassen et al 2012;Hong et al 2014), Twitter (Davenport et al 2014;Kircaburun 2016a;Kim et al 2008), Instagram (Kircaburun and Griffiths 2018a, b), Snapchat (Punyanunt-Carter et al 2017), WeChat (Hou et al 2017), Youtube (Balakrishnan and Griffiths 2017), and social media in general (Andreassen et al 2017;Bányai et al 2017;Kircaburun 2016b;Kircaburun et al 2018a, b). These studies have shown that PSMU is associated with various psychological, personality, and individual difference factors.…”
Section: Uses and Gratificationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, PSMU has been investigated in relation to specific SMSs such as Facebook (Andreassen et al 2012;Hong et al 2014), Twitter (Davenport et al 2014;Kircaburun 2016a;Kim et al 2008), Instagram (Kircaburun and Griffiths 2018a, b), Snapchat (Punyanunt-Carter et al 2017), WeChat (Hou et al 2017), Youtube (Balakrishnan and Griffiths 2017), and social media in general (Andreassen et al 2017;Bányai et al 2017;Kircaburun 2016b;Kircaburun et al 2018a, b). These studies have shown that PSMU is associated with various psychological, personality, and individual difference factors.…”
Section: Uses and Gratificationsmentioning
confidence: 99%
“…YouTube offers a wide variety of opportunities for individuals in the form of active and passive participation, and has achieved previously unthought of levels of social interaction and participation (Khan 2017). Previous studies investigating YouTube use from the U&GT perspective have reported different motivations such as content creation and viewing, social gratification, relaxing entertainment, social interaction, and information seeking (Balakrishnan and Griffiths 2017;Haridakis and Hanson 2009;Khan 2017). In the present study, it is hypothesized that YouTube use will be associated with passing time and task management, as well as entertainment, and informational and educational motives.…”
mentioning
confidence: 99%
“…Social media platforms, as industries profiting from prolific user engagement and information distribution, are mediums that inherently encourage overuse. Restricted self-direction, in combination with youths' innate desire for acceptance and companionship, has fostered some adolescents to rely on social media for validation, resulting in both significant health and psychological issues amongst susceptible users (Balakrishnan & Griffiths, 2017). Previous research suggests that extensive use of social networking tools affects various aspects of users' daily life in terms of psychosomatic well-being, overall health, and family and work life.…”
Section: Social Media and Addictionmentioning
confidence: 99%
“…Interestingly, social media addiction and gratifications vary across platforms. As an example, YouTube is found to be more addicting for content creators than for content viewers (Balakrishnan & Griffiths, 2017). Additionally, gratification was essential for both content consumers and content purveyors in bolstering affinity toward YouTube; specifically, social gratification was found to be significantly related to higher levels of viewership as well as higher levels of creation (ibid).…”
Section: Medium Differencesmentioning
confidence: 99%
“…While some of these studies have focused on the use of social media more generally (Bányai et al 2017;Kırcaburun 2016a;Kircaburun, Alhabash, Tosuntaş, & Griffiths, 2018a;Kircaburun, Demetrovics, & Tosuntaş, 2018b;Kircaburun et al, 2018c;Monacis et al 2017;Wegmann et al 2015), some studies have specifically investigated problematic and addictive use of specific social networking sites such as Facebook (Satici 2018;Young et al 2017), Twitter (Kırcaburun 2016b), and YouTube (Balakrishnan and Griffiths 2017). Although there is no official diagnostic system (e.g., DSM-5; American Psychiatric Association 2013) or widely accepted diagnostic criteria (Spada 2014) for social media disorder, problematic social media use-which is a specific type of problematic Internet use (Griffiths et al 2014)-has been conceptualized as a potential behavioral addiction within a biopsychosocial framework comprising core addiction components (Griffiths 2005).…”
mentioning
confidence: 99%